Effect of working conditions on occupational good health and well-being in construction industry in Klang Valley, Malaysia - Wong, Wei Thong (2023)
The construction industry is characterized by demanding and challenging working conditions that can have significant implications for the well-being of its employees. This research study sought to explore the intricate relationship between working conditions and occupational good health and well-being within the context of the construction industry. Utilizing a survey questionnaire, data were gathered from employees, with a specific focus on the independent variables of demand, control, change, and support, and their potential impact on occupational good health and wellbeing. The findings of the study unveiled compelling insights into the associations between specific working conditions and occupational well-being. Notably, higher levels of demand and support demonstrated positive correlations with improved wellbeing, indicating the importance of adequately managing job demands and fostering a supportive work environment for employees. Conversely, the results indicated a negative correlation between change and well-being, emphasizing the significance of effective change management strategies in mitigating potential adverse effects on employee well-being. However, the study did not identify a significant correlation with control, suggesting a need for further exploration into its role in the context of occupational well-being in the construction industry. These results have important implications for practitioners and policymakers in the construction industry. Recommendations include prioritizing job demands and work-life balance, fostering a supportive work environment, implementing effective change management practices, conducting longitudinal studies, and promoting collaboration and knowledge sharing within the industry. By adopting these suggestions, practitioners and policymakers can work towards creating healthier work environments and promoting the well-being of employees in the construction industry.